ASSESSMENT OF THE RISK OF SKIN LESIONS ASSOCIATED WITH DEMODEX MITES IN STUDENTS WITH ACNE VULGARIS - Radko A.; Melekhovets O.; Kharchenko T.; Melekhovets Y. (Eastern Ukrainian Medical Journal, 2020)
The study of comorbid pathologies that influence the severity of the disease and impair the effectiveness of treatment is carried out to optimize the treatment of the main disease.Materials and methods. The total of 132 medical students was divided into two groups: the 1st group: 56 students who didn`t have acne elements, the 2nd group: 76 students with mild acne vulgaris. At the baseline and after 12 months epithelial tape-test was performed to define Demodex mites presence. The theory of chances was used to assess the impact of acne on the occurrence of Demodex mites.Results. The presence of Demodex mites was observed in 3.57% of students in the 1st group and in 21.05% of students in the 2nd group on repeated tape-test. The probability value (P) among students of the 1st group was P1 = 0.037; among students of the 2nd group – P2 = 0.266. The odds (O) indicator in the 1st group of students without acne elements was O1 = 0.04, in the 2nd group diagnosed with acne – O2 = 0.21. The odds ratio (OR) value in the case/control groups was 7.20. Confidence intervals (95% CI) – (1.582, 32.765): the lower limit of the confidence interval (2.019, + ∞); the upper limit of the confidence interval (-∞, 25680). Significance test p-value was 0.00533.Conclusion. Acne vulgaris is one of aggravating factor that increases the risk of Demodex mites.